AWARENESS AND KNOWLEDGE ASSESSMENT OF SUSTAINABLE DEVELOPMENT GOALS AMONG UNIVERSITY STUDENTS - Jati, Hafsah Fajar; Darsono, Susilo Nur Aji Cokro; Hermawan, Dedy Tri; Yudhi, Wahdi April Salasi; Rahman, Ferry Fadzlul (Jurnal Ekonomi & Studi Pembangunan, 2019)
The Sustainable Development Goals (SDGs) are built on the successes of the Millennium Development Goals (MDGs), which consists of 17 goals as a universal call to action to end poverty, protect the planet, and ensure that all people enjoy peace and prosperity. The assessment of people’s awareness and knowledge on SDGs is of paramount importance to support any subsequent actions. The awareness of SDGs is higher compared to the previous agenda MDGs only in particular emerging countries; hence, it requires better progress after more than three years of its establishment. University students, as the agent of changes, are supposed to have a higher level of awareness and knowledge rather than average. When the university students have a better awareness and higher knowledge on SDGs, they can actively contribute to support, promote, and achieve the development goals by making use of their academic background. The objective of this research is to assess the level of awareness and knowledge on Sustainable Development Goals (SDGs) among university students in Universitas Muhammadiyah Yogyakarta, Indonesia. Data for this research are collected by field Survey and Questionnaire. This research analyzes data by using descriptive statistics and Chi-Square. The results show 89.5% of students are aware and 62.5% of students have high knowledge about SDGs. We found that students’ knowledge is only affected by the accessibility of information and students’ awareness is related to not only accessibility of information but also gender. Both awareness and knowledge are not affected by students’ participation in the organization.